Genome-Wide Analysis of Ruminant Staphylococcus aureus Reveals Diversification of the Core Genome - Ben Zakour, Nouri L. (American Society for Microbiology (ASM), 2008)
Staphylococcus aureus causes disease in humans and a wide array of animals. Of note, S. aureus mastitis of ruminants, including cows, sheep, and goats, results in major economic losses worldwide. Extensive variation in genome content exists among S. aureus pathogenic clones. However, the genomic variation among S. aureus strains infecting different animal species has not been well examined. To investigate variation in the genome content of human and ruminant S. aureus, we carried out whole-genome PCR scanning (WGPS), comparative genomic hybridizations (CGH), and the directed DNA sequence analysis of strains of human, bovine, ovine, and caprine origin. Extensive variation in genome content was discovered, including host- and ruminant-specific genetic loci. Ovine and caprine strains were genetically allied, whereas bovine strains were heterogeneous in gene content. As expected, mobile genetic elements such as pathogenicity islands and bacteriophages contributed to the variation in genome content between strains. However, differences specific for ruminant strains were restricted to regions of the conserved core genome, which contained allelic variation in genes encoding proteins of known and unknown function. Many of these proteins are predicted to be exported and could play a role in host-pathogen interactions. The genomic regions of difference identified by the whole-genome approaches adopted in the current study represent excellent targets for studies of the molecular basis of S. aureus host adaptation.